2021
DOI: 10.21037/apm-21-2537
|View full text |Cite
|
Sign up to set email alerts
|

Mortality prediction using clinical and laboratory features in elderly patients with severe community-acquired pneumonia

Abstract: Background: Severe community-acquired pneumonia (SCAP) is a serious health threat in elderly individuals, and a prospective, observational study was conducted to explore the prognostic factors.Methods: Patients (≥65 years old) with SCAP that had an intensive care unit (ICU) stay >24 h were recruited at our center. Clinical and laboratory data were collected and various assessment scores were calculated. The follow-up period was censored at the date of death or at hospital discharge, whichever came first.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Several studies have revealed that decreased CD4 + T cells indicate higher mortality. In a study enrolled 120 elderly SCAP patients, decreased CD4 + T cells were independent prognostic factors of mortality 8 . Similarly, a recent study about elderly patients with pneumonia showed that lower levels of CD4 + T cells were observed in the early deceased group than the late deceased patients or survivors 27 .…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Several studies have revealed that decreased CD4 + T cells indicate higher mortality. In a study enrolled 120 elderly SCAP patients, decreased CD4 + T cells were independent prognostic factors of mortality 8 . Similarly, a recent study about elderly patients with pneumonia showed that lower levels of CD4 + T cells were observed in the early deceased group than the late deceased patients or survivors 27 .…”
Section: Discussionmentioning
confidence: 86%
“…Several studies have been conducted in elderly patients, and found the relationship between CAP and various subtype T cells, such as CD4 + T cells and Treg cells. In a recent study, elderly SCAP patients showed lower CD4 + T cells in survival group than that of mortality group 8 …”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…When we classified the type of mechanical ventilation as invasive ventilation or not, there was a significant difference between co-infection and ICU-acquired infection (p = 0.003). The length of ICU stay for patients with co-infection was 14 days (Range, 7.5-26.5) while that for patients with ICU-acquired infection was 24 days (Range, [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32], and further analysis revealed that there was a borderline significant difference in the length of ICU stay between these two groups (p = 0.079). Besides, 18 patients (38.30%) were death and 29 (61.70%) alive in day-28.…”
Section: Demographic and Clinical Characteristicsmentioning
confidence: 99%
“…To further investigate the sources of heterogeneity, we performed subgroup analyses of studies related to COVID-19 and studies related to other pathogens. We found that subgroup analysis did not significantly reduce the source of heterogeneity, Juling 2020 [25] RCT [30] RCT Exp-group 43, Age 57 Cont-group 43, Age 55 2020 interim guidance of World Health Organization Methylprednisolone 1.0 mg/kg/d through d 7 Yang Qing 2018 [31] RCT Exp-group 40 [32] RCT Exp-group 30, Age (79. and the results of subgroup analysis showed that glucocorticoids increased the length of hospital stay in patients with COVID-19 (MD = 0.20, CI: 0.02-0.39) (Fig. 6), but glucocorticoids had no effect on the length of hospital stay in patients with sCAP caused by other pathogens (MD = −0.27, CI: −0.60 to 0.06).…”
Section: Length Of Hospital Staymentioning
confidence: 99%